The Future Circle of Healthcare AI, 3D Printing, Longevity, Ethics, and Uncertainty Mitigation - Ehsani, Sepehr; Glauner, Patrick; Plugmann, Philipp; Thieringer, Florian M. (Cham : Springer International Publishing : Imprint: Springer, 2022)
The past decade has brought to the fore the critical need to constantly envision and consider various scenarios where ongoing trends and sudden changes could together alter the provision of healthcare and the direction of medical research. This book brings together scholars whose areas of expertise represent different themes that are essential to understanding how healthcare might change and evolve over the next decade. What lessons can one take away from current and past developments? The themes explored by the book rest on four pillars. The first is the rapid pace and ubiquity of technological advances in areas such as artificial intelligence, machine learning, additive manufacturing and wearable electronics. The second pillar concerns healthy aging, longevity and the management of chronic diseases. The third is the imperative to remain cognizant of the ethical dimensions of medical decisions, adapting bioethics to ongoing changes in healthcare provision. Finally, the fourth pillar relates to how uncertainty in different domains of medical knowledge can be mitigated and translated into clinical practice. For example, how should uncertainty with the results of clinical trials for a new treatment be dealt with? What cost-benefit analyses would be most appropriate for the situation? Chapter authors identify respective challenges and promising opportunities, discussing how these could contribute to envisioning the future scope of healthcare when it comes to providing medical, economic and ethical values to human societies. Chapters 1, 4, 12, and 20 are available open access under a Creative Commons Attribution 4.0 International License via link.springer.com.
Chapter 1. Introduction - Trends, Puzzles and Hopes for the Future of Healthcare -- Chapter 2. Innovations in Psychiatric Care Models: Lessons from the Past to Inform the Future -- Chapter 3. Mobile Sensors in Healthcare: Technical, Ethical, and Medical Aspects -- Chapter 4. New Horizons in Studying the Cellular Mechanisms of Alzheimer's Disease -- Chapter 5. Harnessing AI and Genomics to Accelerate Drug Discovery -- Chapter 6. Ethical Challenges in Applying New Technologies in Orthopedic Surgery -- Chapter 7. An Assessment of the AI Regulation Proposed by the European Commission -- Chapter 8. Post-Truth Implications for COVID-Era Healthcare: Verification, Trust, and Vaccine Skepticism -- Chapter 9. Patents on Inventions Involving AI in the Life Sciences and Healthcare -- Chapter 10. Redesigning Relations: Coordinating Machine Learning Variables and Sociobuilt Contexts in COVID-19 and Beyond -- Chapter 11. Sensor Devices, the Source of Innovative Therapy and Prevention -- Chapter 12. Digital and Computational Pathology: A Specialty Reimagined -- Chapter 13. Modern Home Care: A Glimpse into the Future of Patient-Centered Healthcare Systems -- Chapter 14. Teledermatology: Current Indications and Future Perspectives -- Chapter 15. Using Artificial Intelligence for the Specification of m-Health and e-Health Systems -- Chapter 16. The Outlook for Novel Pharmaceutics -- Chapter 17. The Future Open Innovation Approach in Health Care Needs Patients' Support -- Chapter 18. Uncertainty in Medicine: An Active Definition -- Chapter 19. Innovations for Sustainable Healthcare -- Chapter 20. Medical Additive Manufacturing in Surgery - Translating Innovation to the Point-of-Care -- Chapter 21. The Future of Medical Education -- Chapter 22. Personalized Dental Medicine with Specific Focus on the Use of Data from Diagnostic Dental Imaging.
Keywords: Health services administration; Technological innovations; Artificial intelligence; Medical sciences; Health Care Management; Innovation and Technology Management; Artificial Intelligence; Health Sciences